Optimizing Classroom Youtube Channel As A Learning Platform To Encourage Students Speaking Practice - Astuti, Sari (JOLADU: Journal of Language Education, 2022)
YouTube as has become undeniable learning sources for students and teachers. It provides them with abundant videos that can support online and offline learning process. Besides exposing to audio visual media, YouTube enable students to display their speaking videos and get respond from teachers and friends. The respond can be in the form of giving a thumb or positive comment to their speaking performance. This can boost students motivation and confident in creating videos and encourage them to practice speaking. Therefore, this study proposes the idea of utilizing Classroom YouTube channel to encourage students’ speaking practice by allowing them to upload their videos, watching their friends’ speaking performance, collaborate, and learn to have online interaction and appreciation to their friends’ speaking performance. Further, it shows the steps of activating classroom YouTube channel to be an interactive learning platform and the procedures in an online classroom based on its theoretical perspectives